Combining Ability for Yield, Yield Components, and Agronomic traits in Super Sweet Corn Inbred Lines Derived from Exotic - Harakotr , Bhornchai; Thongkham, Kanokwan; Jirakriattikul, Yaowapa (Thai Journal of Science and Technology, 2022)
The study of combining ability is important to determine the potential of inbred and hybrid corn. Therefore, the objective of this study was to study combining ability in super sweet corn inbred lines derived from exotic germplasm. Seven super sweet corn inbred lines were crossed in a diallel cross mating design. The parental lines, 42 hybrids, and 2 commercial varieties were evaluated in the winter season of 2020/2021. The experiment was arranged in a randomized complete block design with 2 replications. The results indicated that variations of the dominant gene were more than additive gene effects for all studied traits except cob length, total soluble solid, plant height, and cob replacement height, and then selection of these traits should be select in late generation. L4 line had high general combining ability (GCA) for yield, whereas L1 and L2 lines had a high GCA value for cutting percentage and total soluble solids, respectively. Moreover, L2/L5, L4/L5, L4/L7, and L7/L2 hybrids had high yields and specific combining ability, which were not different with the commercial varieties. The results revealed that super sweet corn inbred lines derived from exotic germplasm have the potential to develop as parental lines and be produce new hybrids with high yields and good agronomic traits in the future.